Establishment of a zebrafish hematological disease model induced by 1,4-benzoquinone - Ao Zhang; Mei Wu; Junliang Tan; Ning Yu; Mengchang Xu; Xutong Yu; Wei Liu; Yiyue Zhang (The Company of Biologists, 2019)
Benzene exposure is associated with various hematological disorders, in particular leukemia. The reactive metabolite of benzene, 1,4-benzoquinone (BQ), generated in bone marrow, is suggested to be a key molecule in mediating benzene-induced hematotoxicity and carcinogenicity. However, its pathogenic role remains largely unknown due to a lack of suitable vertebrate whole-organism models. Here, we present an in vivo study to reveal the effect of BQ exposure on hematotoxicity in zebrafish. From embryonic stages to adulthood, BQ exposure suppressed erythroid and lymphoid hematopoiesis but led to abnormal accumulation of myeloid cells and precursors, which resembles benzene-induced cytopenia and myeloid dysplasia in humans. This myeloid expansion is caused by granulocyte, but not macrophage, lineage, emphasizing the significant role of lineage specificity in BQ-mediated hematopoietic toxicity. Analysis of the c-myb (also known as myb)-deficient mutant cmybhkz3 revealed that BQ induced neutrophilia in a c-myb-dependent manner, demonstrating that c-myb is a key intrinsic mediator of BQ hematotoxicity. Our study reveals that BQ causes lineage-specific hematotoxicity in zebrafish from embryonic stages to adulthood. Since c-myb is indispensable for BQ to induce neutrophilia, c-myb could serve as a potential drug target for reversing BQ hematotoxicity.